Metodologia de Self-healing aplicada à redes de distribuição considerando recursos energéticos distribuídos - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Electric power distribution systems are experiencing significant changes due to the insertion of new technologies and new concepts for generation. In this context of the constantly changing, the Smart Grids have a great potential for innovation in distribution networks, as they provide more reliability and quality to distribution systems. One of the main concepts, coming from Smart Grids is the concept of Self-healing, which is an important tool for the recovery of networks when the contingency occur. Through a Self-healing system, it is possible to reduce the losses to the eletric utility and the consumers caused by network failures, there by making the distribution network more secure, reliable and delivering quality energy to consumers. An important ally for the implementation of Self-healing systems is the distributed energy resources, since these are an important tool for the development of the distribution networks, allowing more exibility to the systems, especially when it is necessary to carry out maneuvers for load transfer when contingency occur on distribuition grid. In the face of the above, this paper will presents the development of a methodology for the analysis of Self-healing systems in distribution networks with distributed energy resources, formed by photovoltaic panels and electrical energy storage systems. Although the objective of the methodology is minimization of electrical losses and reduction of consumer units hit by a network failure. In addition, in this work the AHP algorithm was used to develop the methodology of Self-healing, this algorithm was used with the purpose of deciding which maneuvers were most suitable according to the objectives desired by the methodology. Thus, the performance of the proposed methodology was veried through the OpenDSS software, in a IEEE 34 bars system modified. Two tests was performed, which considered the variation of the load throughout the day. In the first test, it was performed through a fault in the distribution network that occurred in an area with predominant residential load. Already the second test was simulated by means of a fault in the distribution network in a predominant industrial area.
Keywords: Engenharia elétrica; Redes de distribuição de energia elétrica; Painéis fotovoltaicos; Smart Grids; Self-healing; Electrical engineering; Electricity distribution networks; Photovoltaic panels; CNPQ::ENGENHARIAS